The 1994 Hutu and Tutsi Ethnopolitics Conflict in Rwanda: Genocide Revenge Settlement Through the Gacaca Reconciliation System - Probo Darono Yakti (Jurnal Hubungan Internasional, 2022)
The conflict between the Hutu and Tutsi tribes that occurred in Rwanda at the end of the 20th century opened the eyes of the international community that ethnic issues could escalate into a political issue which encouraged the crime of genocide. This politicization led to the deaths of more than 800 thousand Tutsis due to planned mass killings by the Hutu government. This justifies Gilroy and Wright's argument about ethnic politicization which can form an exclusive feeling in talking about one's nationality within the state. Likewise with Yun and Synder's opinion about racial issues affecting people's political preferences on a large scale and tend to see negative forms of nationalism when viewed from ethnicity. By using a discourse analysis and qualitative-explanatory research approach, a comprehensive approach is obtained to understand the problem in its entirety and explore the research questions: how to explain the conflict in Rwanda between the Hutu and Tutsi tribes from the aspect of politicizing the identity issue in the era of postcolonialism? In this paper, a number of issues will be raised, namely the fundamental differences between the Hutu and Tutsi, the chronology of the conflicts between the two tribes, the spread of these problems into regional conflicts, investigating the causes, settlement methods, and post-conflict life in Rwanda. So that it concludes that it is true that there is ethnic politicization in Rwanda. The importance of this paper is to be a lesson for other regions of the world that experience the same problems and can offer options for methods of conflict resolution as has been done by Rwanda: reconciliation, accommodation, and the Gacaca system. These four methods require a long process and a sense of relief from each individual community to forgive the actions of their own neighbors who become murderers for their own neighbors. So it is important to make lessons for conflicts based on other ethnic differences.